THE INFLUENCE OF SERVICE QUALITY AND PHYSICAL ENVIRONMENT TOWARDS CUSTOMER SATISFACTION WITH PRICE AS MODERATOR IN COFFEE SHOP IN MEDAN - Steffani Chandra; Daniel Cassa Augustinus (Faculty of Economics and Business Universitas Pelita Harapan, 2022)
The food and beverage industry are continually evolving. To acquire competitive advantages such as customer satisfaction, it is critical to provide the best service quality and physical environment. Meanwhile price sometimes will moderate the perception of both factor towards customer satisfaction. Conducted at Warung Kopi Srikandi Medan, this research is aimed to describe how the price moderate relationship between service quality, physical environment, and customer satisfaction. In this research, the writer is using the quantitative method, descriptive, and causal techniques. Choosing customers of Warung Kopi Srikandi Medan become the sample with the convenience sampling method. The findings of this research show that service quality and physical environment had a significant influence and simultaneous influence on customer satisfaction. Meanwhile Price become a moderator of relationship between service quality and physical environment towards customer satisfaction. However, physical environment does not influence customer satisfaction partially.